2016
DOI: 10.1002/ange.201609439
|View full text |Cite
|
Sign up to set email alerts
|

Modelling a Linker Mix‐and‐Match Approach for Controlling the Optical Excitation Gaps and Band Alignment of Zeolitic Imidazolate Frameworks

Abstract: Tuning the electronic structure of metal–organic frameworks is the key to extending their functionality to the photocatalytic conversion of absorbed gases. Herein we discuss how the band edge positions in zeolitic imidazolate frameworks (ZIFs) can be tuned by mixing different imidazole‐based linkers within the same structure. We present the band alignment for a number of known and hypothetical Zn‐based ZIFs with respect to the vacuum level. Structures with a single type of linker exhibit relatively wide band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Figure shows a popular member – ZIF‐8, an archetypal example of MOF's resistance to pressure . ZIF‐8 is also a choice system for modeling studies, aimed at the molecular‐level description of the geometry and flexibility of the pore windows, useful in sorption applications, or the modification of its band structure for electronic or photocatalytic uses ,…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…Figure shows a popular member – ZIF‐8, an archetypal example of MOF's resistance to pressure . ZIF‐8 is also a choice system for modeling studies, aimed at the molecular‐level description of the geometry and flexibility of the pore windows, useful in sorption applications, or the modification of its band structure for electronic or photocatalytic uses ,…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…In ZIF-8, the valence band is localized in the N atoms from the two amine groups, while the conduction band is formed by the empty orbitals of Zn. 42 Thus, any photogenerated electrons will travel to the Zn cluster and from there to the NRs by a process known as ligand-to-cluster charge transfer 43 (LCCT). Meanwhile, holes will be injected through the amine groups into water molecules adsorbed to shell hydrogens, initiating the water-splitting process as represented by the black and yellow schematic on the right side of the electronic band diagram of Figure 5 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…These authors showed that incorporation of the cerium cation presents an effective way not only to stabilize the LMCT, but also to increase the photocatalytic activity of UiO-66 MOF [49]. For applications in photocatalysis, the magnitude of the band gap and the absolute positions of the band edges are of high importance [50,51]. As an example, based on the mixing of organic linkers, Ricardo et al have designed new ZIF materials with a narrower band gap in order to allow the absorption of the visible range solar spectrum.…”
Section: (D) Describing Excited Statesmentioning
confidence: 99%
“…As an example, based on the mixing of organic linkers, Ricardo et al have designed new ZIF materials with a narrower band gap in order to allow the absorption of the visible range solar spectrum. They showed that by introducing a transition metal (copper) in the tetrahedral position of the mixed-linker ZIFs, it is possible to increase photo-adsorption [51].…”
Section: (D) Describing Excited Statesmentioning
confidence: 99%